Pulmonary edema following generalized tonic clonic seizures is directly associated with seizure duration. (April 2015) - Kennedy, Jeffrey D.; Hardin, Kimberly A.; Parikh, Palak; Li, Chin-Shang; Seyal, Masud
Highlights: Chest X-rays (CXR) obtained following generalized tonic clonic seizures in EMU. Postictal pulmonary edema found in 7 of 24 patients. Preceding seizure duration was longer when CXR was abnormal versus normal CXR. Odds-ratio for abnormal X-ray was 20.46 when seizure duration exceeded 100 s. Postictal pulmonary edema may be relevant in the pathophysiology of SUDEP. Abstract: Purpose: Postictal pulmonary edema (PPE) is almost invariably present in human and animal cases of sudden unexpected death in epilepsy (SUDEP) coming to autopsy. PPE may be a contributing factor in SUDEP. The incidence of postictal PPE is unknown. We retrospectively investigated PPE following generalized tonic clonic seizures (GTCS) in the epilepsy monitoring unit. Method: Chest X-rays (CXR) following each GTCS were obtained in 24 consecutive patients. Relationship of CXR abnormality to seizure duration, ictal/postictal oxygen desaturation (SpO2), apnea and presence of postictal generalized EEG suppression (PGES) was investigated using logistic regression. Results: Eleven of 24 patients had CXR abnormalities following a GTCS. In these 11 patients, 22 CXR were obtained and abnormalities were present in 15 CXR. Abnormalities included PPE in 7 patients, of which 2 also had focal infiltrates. In 4 patients focal infiltrates were present without PPE. There was no significant difference in mean time to CXR (225 min) following GTCS in the abnormal CXR group versus the normal group of patients (196 min). Mean preceding seizure duration was longer ( p  = 0.002) in GTCS with abnormal CXR (259.7 s) versus GTCS with normal CXR (101.2 s). Odds-ratio for CXR abnormality was 20.46 ( p  = 0.006) with seizure duration greater than 100 s versus less than 100 s. On multivariable analysis, only the seizure duration was a significant predictor of CXR abnormality ( p  = 0.015). Conclusion: Radiographic abnormalities are not uncommon following GTCS. The presence of CXR abnormality is significantly associated with the duration of the preceding GTCS. Severe, untreated PPE may be relevant to the pathophysiology of SUDEP.